Pengaruh Partisipasi Penganggaran, Informasi Asimetri, Komitmen Organisasi, dan Ketidakpastian Lingkunganpada Senjangan Anggaran - Cahyadi Luhur, Ida Bagus Surya; Supadmi, Ni Luh (E-Jurnal Akuntansi, 2019)
Budget is an important part in the activities of both the public and corporate sectors. Sector sector sector sector sector sector Organization Organization Organization Organization Organization Organization Organization Organization Organization Organization Organization Organization Organization can be factor factor factor factor factor factor factor objective The purpose of this research is to find information about budgeting, information asymmetry, commitment organization, and environmental uncertainty on budgetary slack. The population of this research is Regional Device Organization (OPD) in the scope of Denpasar City Government which amounts to 33 OPD, the number of samples obtained by respondents is 99 OPD employees. Data analysis techniques are multiple regression analysis. The results of this study indicate that budgeting activities, information asymmetry, organizational commitment, and environmental and environmental uncertainty in the City Device Agency (OPD) within the scope of the Denpasar City Government. Keywords: Budgeting participation, information asymmetry, organizational commitment, environmental uncertainty, budgetary slack.